Your Dream Vacation - Evento, Susan (NewYork Cambridge University, 2014)
How do you want to spend your vacation? Relaxing on a beach, whitewater rafting, at the carnival in Rio? Dream about your perfect vacation as you read!
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Elementary level